Men with High Prostate Specific Antigen Have Higher Risk of Gleason Upgrading after Prostatectomy: A Systematic Review and Meta-analysis - Wang, Xiaochuan; Zhang, Yu; Ji, Zhengguo; Yang, Peiqian; Tian, Ye (Urology Journal, 2020)
Purpose: To examine the correlation between prostate specific antigen (PSA) and the risk of Gleason sum upgrading (GSU) from biopsy Gleason sum (bGS) to prostatectomy Gleason sum (pGS). Materials and Methods: Five electronic databases (Web of Science, Ovid Medline, Ovid Embase, SCOPUS and the Cochrane Library) were searched from inception until March 2020. Studies were included if they focused on the relationship between PSA and GSU analyzed in multivariable analysis. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were utilized. Quality of included studies was appraised utilizing the Newcastle-Ottawa Quality Assessment Scale (NOS) for case-control studies. The publication bias was evaluated by funnel plot and Egger’s test. Results: Our search yielded 19 studies with high quality including 42193 patients. GSU was found in 28.2% of patients. Higher PSA level was associated with a significant increased risk of GSU (pooled OR = 1.14, 95% CI: 1.10–1.18; P < .05; I2 = 92%). For the definition of upgrading from bGS ≤ 6 to pGS ≥ 7, the odds of upgrading with higher PSA level as opposed to lower PSA level was 1.12 (95% CI: 1.11–1.14; P < .05; I2 = 13%), while the odds of upgrading with other definitions were 1.11 (95% CI: 1.05–1.18; P < .05; I2 = 89%). Conclusion: Patients with high level of serum PSA are at high risk of undergoing pathologic upgrading at prostatectomy. Combined with other risk factors, PSA prompts risk reclassification and improve confidence of urologists in management decisions for optimal therapy. Nevertheless, further robust studies are necessitated to confirm these results.